2022
DOI: 10.1093/ckj/sfac060
|View full text |Cite
|
Sign up to set email alerts
|

Kidney–placenta crosstalk in health and disease

Abstract: Organ crosstalk allows the interaction between systems to adapt to a constant changing environment, maintaining homeostasis. The process of placentation and the new hormonal environment during pregnancy trigger physiological changes that modulate kidney function to control extracellular volume, acid-base balance, and filtration of metabolic waste products. The bidirectional communication means that acute or chronic dysfunction of one organ can compromise the other. Abnormal placentation in pregnancy-related hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Previous research, including our own, has identified Stroke-Prone Spontaneously Hypertensive rats as a suitable model for investigating chronic hypertension during pregnancy [ 23 , 25 27 ]. Abnormal placentation leads to the release of antiangiogenic factors that may cause subclinical kidney injury [ 28 ]. We and others have shown abnormal placentation with release of antiangiogenic factors and kidney injury in Stroke-Prone Spontaneously Hypertensive rats [ 26 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research, including our own, has identified Stroke-Prone Spontaneously Hypertensive rats as a suitable model for investigating chronic hypertension during pregnancy [ 23 , 25 27 ]. Abnormal placentation leads to the release of antiangiogenic factors that may cause subclinical kidney injury [ 28 ]. We and others have shown abnormal placentation with release of antiangiogenic factors and kidney injury in Stroke-Prone Spontaneously Hypertensive rats [ 26 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%